Onstage Violence in Sixteenth-Century French Tragedy - Meere, Michael (Oxford University Press USA - OSO, 2021)
Studies the representation of violence in tragedies written for the French stage during the sixteenth century, and explores its connection with issues such as politics, religion, gender, and militantism to place the plays within their historical, cultural, and theatrical contexts.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Violence in literature; Violence in the theater; French drama-16th century-History and criticism